Influence of acid-etching and ceramic primers on the repair of a glass ceramic - Queiroz, J. R C [UNESP]; Souza, Rodrigo O.A.; Nogueira, L.; Ozcan, M.; Bottino, M. A. (My University, 2012)
The objective of this study was to evaluate the influence of different primers on the microtensile bond strength (μT BS) between a feldspathic ceramic and two composites. Forty blocks (6.0 × 6.0 × 5.0 mm 3) were prepared from Vita Mark II . After polishing, they were randomly divided into 10 groups according to the surface treatment: Group 1, hydrofluoric acid 10% (HF) + silane; Group 2, CoJet + silane; Group 3, HF + Metal/Zirconia Primer; Group 4, HF + Clearfil Primer; Group 5, HF + Alloy Primer; Group 6, HF + V-Primer; Group 7, Metal/Zirconia Primer; Group 8, Clearfil Primer; Group 9, Alloy Primer; Group 10, V-Primer. After each surface treatment, an adhesive was applied and one of two composite resins was incrementally built up. The sticks obtained from each block (bonded area: 1.0 mm2 ± 0.2 mm) were stored in distilled water at 37°C for 30 days and submitted to thermocycling (7,000 cycles; 5°C/55°C ± 1°C). The μT BS test was carried out using a universal testing machine (1.0 mm/min). Data were analyzed using ANOVA and a Tukey test (α = 0.05). The surface treatments significantly affected the results (P < 0.05); no difference was observed between the composites (P > 0.05). The bond strength means (MPa) were as follows: Group 1a = 29.6; Group 1b = 33.7; Group 2a = 28.9; Group 2b = 27.1; Group 3a = 13.8; Group 3b = 14.9; Group 4a = 18.6; Group 4b = 19.4; Group 5a = 15.3; Group 5b = 16.5; Group 6a = 11; Group 6b = 18; Groups 7a to 10b = 0. While the use of primers alone was not sufficient for adequate bond strengths to feldspathic ceramic, HF etching followed by any silane delivered higher bond strength.
Keywords: Alloy Primer; aluminum silicate; dental material; Filtek Supreme; Glass ceramics; hydrofluoric acid; Metal Primer; methacrylic acid derivative; potassium derivative; resin; resin cement; Scotchbond Multi Purpose; Scotchbond Multi-Purpose; silane derivative; thioketone; triazine derivative; V Primer; V-Primer; Vita Mark II; water; ceramics; chemistry; comparative study; controlled clinical trial; controlled study; dental acid etching; dental bonding; dental porcelain; dental procedure; feldspar; human; instrumentation; materials testing; mechanical stress; methodology; randomized controlled trial; scanning electron microscopy; surface property; temperature; tensile strength; time; tooth brushing; tooth prosthesis; Acid Etching, Dental; Aluminum Silicates; Ceramics; Composite Resins; Dental Bonding; Dental Materials; Dental Polishing; Dental Porcelain; Dental Prosthesis Repair; Dental Stress Analysis; Humans; Hydrofluoric Acid; Materials Testing; Methacrylates; Microscopy, Electron, Scanning; Potassium Compounds; Resin Cements; Silanes; Stress, Mechanical; Surface Properties; Temperature; Tensile Strength; Thiones; Time Factors; Triazines; Water